Paradoxical paradigms: moral reasoning, inspiration, and problems of knowing among Orthodox Christian monastics. (May 2015) - Forbess, Alice; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> Whilst anthropological discussions of morality tend to be rooted in Aristotelian ethical theory, this paper highlights an alternative Christian moral reasoning rooted in Neoplatonist/Christian hybrids and visible in contemporary Eastern Orthodox monastic practice. The analytical move proposed here is to focus on the disjunctures between different ethical traditions within Christianity in order to show how they produce diverse forms of moral reasoning that rely on particular uses of exemplarity and exemplification. It is argued that the Aristotelian lens, with its stress on compliance, piety, obedience, and the daily practice of self‐perfection, can produce impoverished accounts of ascetic life by excluding the more anarchic and idiosyncratic forms of spiritual training. Christianity has a long tradition of deploying paradox and perplexity to explode facile certainties, thereby carving out a space, at the limits of human knowing, where a divinity conceived as radically alter to the created world can be directly engaged with.